Control of Head-Tilting Angle of the Diamagnetically Levitated Microrobot in Liquid Media - Demircali, Ali Anil; Yilmaz, Cesur Atay; Uvet, Huseyin (IEEE, 2018)
In this work, open-loop and closed-loop lateral movement control of a microrobot in a liquid environment(DI-water) is presented. During the lateral movement of a diamagnetically levitated microrobot, the drag force caused by the fluid interaction must be minimized in order to increase the precision of localization. The magnitude of the drag force varies depending on the speed of the microrobot and its hydrodynamic structure. A new control technique has been developed and implemented to minimize the friction force to make the lateral movement more stable. Control techniques are accomplished with the help of a single ring-shaped neodymium magnet lifter magnet (40 mm x 20 mm x 8 mm) with a lower magnetic force requirement. For positioning the lifter magnet, microstages capable of nano-precise motion in x, y and z axes are used. Another disk-shaped magnet is used in the center of the microbobot which is called a carrier magnet. With the developed vision based control mechanisms, the inability to move parallel to the surface of the microrobot head tilting reaction angle is reduced. As a result of an analysis with FEM program (COMSOL (R)), the open loop and closed loop angle equations related to stage speed and orbit distance are obtained by taking into consideration the mechanical delays. With these equations used in open and closed loop control, the head-tilting angle at low speeds ( 2 mm/s) to 3.22 degrees for open-loop control and 1.926 degrees with closed loop control.
Keywords: Diamagnetic Levitation; Microrobot control; Image processing; MAGNETIC MICROROBOT; Automation & Control Systems; Robotics